The Effect of Working Capital, Business Scale, and Labor on the Income of Dairy Farmers in Boyolali Regency - Wulandari, Wulandari; Susilowati, Heni (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the influence of working capital, business scale, and labor availability on the income of dairy farmers in Boyolali Regency. This study applies a quantitative descriptive and analytical approach with a sample of 60 dairy farmers who are members of the Cepogo Cooperative (KUD) taken using a purposive sampling method. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using multiple linear regression using the SPSS program. The findings of this study describe that "working capital, business scale, and labor have a positive and significant effect on the income of dairy farmers." The availability of adequate working capital allows farmers to optimize production activities, while a larger business scale increases efficiency and profits. In addition, a skilled and sufficient workforce supports operational effectiveness, which has a direct impact on increasing income. These findings emphasize the importance of access to capital, expanding business scale, and developing human resources as basic strategies to improve the welfare and competitiveness of local dairy farmers.